(untitled) (World Bulletin of Social Sciences, 2025)
This article examines effective methods for developing primary school students’ ability to comprehend and analyze literary texts. It analyzes the role of modern pedagogical approaches, interactive methods, and graphic organizers in the development of reading literacy. Special attention is given to fostering critical thinking, comparison skills, and the ability to draw conclusions while working with literary texts. The materials presented in the article are recommended for use in primary education practice.